Total knee arthroplasty combined with medial patellofemoral ligament augmentation using a Leeds-Keio ligament for 'Windswept deformity' with ipsilateral valgus deformity and permanent patellar dislocation: A case report and a literature review - Nobuyuki Kumahashi; Suguru Kuwata; Hiroshi Takuwa; Yuji Uchio (Elsevier, 2021)
We present a 'Windswept deformity' in patient who had osteoarthritis with a mild varus and very severe valgus with ipsilateral permanent patellar dislocation. An 83-year-old woman could not walk for the past a few years due to bilateral knee pain. The femorotibial angle was 196° in the right knee pre-operatively and 134° in the left knee with permanent patellar dislocation. She underwent a staged total knee arthroplasty (TKA) for the right knee, and a semi-constrained TKA for the left knee with medial patellofemoral ligament (MPFL) augmentation using a Leeds-Keio (LK) ligament. At the final follow-up three years after surgery, bilateral knee pain and the extension lag had disappeared and range of motion (ROM) was 0° in extension and 130° in flexion for both knees without patellar re-dislocation. This clinical case indicates that the unconstrained and semi-constrained type of TKA combined with the MPFL augmentation using an LK ligament is effective to treat a 'Windswept deformity'.